Cultural Marxism in Postwar Britain : History, the New Left, and the Origins of Cultural Studies - Dworkin, Dennis L., 1951- (Book collections on Project MUSE., 1997)
In this intellectual history of British cultural Marxism, Dennis Dworkin explores one of the most influential bodies of contemporary thought. Tracing its development from beginnings in postwar Britain, through its various transformations in the 1960s and 1970s, to the emergence of British cultural studies at Birmingham, and up to the advent of Thatcherism, Dworkin shows this history to be one of a coherent intellectual tradition, a tradition that represents an implicit and explicit theoretical effort to resolve the crisis of the postwar British Left. Limited to neither a single discipline nor a particular intellectual figure, this book comprehensively views British cultural Marxism in terms of the dialogue between historians and the originators of cultural studies and in its relationship to the new left and feminist movements. From the contributions of Eric Hobsbawm, Christopher Hill, Rodney Hilton, Sheila Rowbotham, Catherine Hall, and E.P. Thompson to those of Perry Anderson, Barbara Taylor, Raymond Williams, Dick Hebdige, and Stuart Hall, Dworkin examines the debates over issues of culture and society, structure and agency, experience and ideology, and theory and practice. The rise, demise, and reorganization of journals such as The Reasoner, The New Reasoner, Universities and Left Review, New Left Review, Past and Present, are also part of the history told in this volume. In every instance, the focus of Dworkin's attention is the intellectual work seen in its political context. Cultural Marxism in Postwar Britain captures the excitement and commitment that more than one generation of historians, literary critics, art historians, philosophers, and cultural theorists have felt about an unorthodox and critical tradition of Marxist theory.